Postcolonialism : an historical introduction - Young, Robert, 1950- 4 0 16; 5 (Chichester, West Sussex, UK ;;Malden, MA : Wiley Blackwell, 2016)
This book is concerned with the revolutionary history of the non-Western world and its centuries-long struggle to overthrow Western imperialism: from slow beginnings in the eighteenth century, the last half of the twentieth century witnessed more than a quarter of the world's population win their freedom. It was written before the momentous political events of the twenty-first century: published two months before the 9/11 attacks in 2001, and ten years before the Arab revolutions that erupted across the Arab world in 2011. It had been originally commissioned as an introduction to postcolonialism at a time when 'postcolonial theory' formed an innovative body of thinking that was making waves beyond its own disciplinary location. That interest was the mark of a new phase within many Western societies in which immigrants from the global South had begun to emerge as influential cultural voices challenging the basis of the manner in which European and North American societies represented themselves and their own histories. The late Edward Said and Stuart Hall both symbolized the ways in which intellectuals who had been born in former colonies became spokespersons for a popular radical re-evaluation of contemporary culture: a profound transformation of society and its values was underway. That revolution involved the consensus of an equality amongst different people and cultures rather than the hierarchy that had been developed since the beginning of the nineteenth century as a central feature of Western imperialism. Postcolonial critique has been so successful--Provided by publisher.
Preface to the Anniversary Edition -- Preface to the First Edition -- Colonialism and the Politics of Postcolonial Critique -- Part I. Concepts in History -- Colonialism -- Imperialism -- Neocolonialism -- Postcolonialism -- Part II. European Anti-colonialism -- Las Casas to Bentham -- Nineteenth-century Liberalism -- Marx on Colonialism and Imperialism -- Part III. The Internationals -- Socialism and Nationalism : The First International to the Russian Revolution -- The Third International, to the Baku Congress of the Peoples of the East -- The Women's International, the Third and the Fourth Internationals -- Part IV. Theoretical Practices of the Freedom Struggles -- The National Liberation Movements : Introduction -- Marxism and the National Liberation Movements -- China, Egypt, Bandung -- Latin America I : Mari tegui, Transculturation and Cultural Dependency -- Latin America II : Cuba: Guevara, Castro and the Tricontinental -- Africa I : Anglophone African Socialism -- Africa II : Nkrumah and Pan-Africanism -- Africa III : The Senghors and Francophone African Socialism -- Africa IV : Fanon/Cabral -- The Subject of Violence : Algeria, Ireland -- India I : Marxism in India -- India II : Gandhi's Counter-modernity -- Part V. Formations of Postcolonial Theory -- India III : Hybridity and Subaltern Agency -- Women, Gender and Anti-colonialism -- Edward Said and Colonial Discourse -- Foucault in Tunisia -- Subjectivity and History : Derrida in Algeria -- Epilogue: Tricontinentalism, for a Transnational Social Justice.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: 2 -- 0; 6; History.;Philosophy.;History.;History.;History.;History.;Emigration & Immigration. -- Postcolonialism;Postcolonialism;Colonies;Imperialism;Revolutions;Anti-imperialist movements;SOCIAL SCIENCE; Politics and government. -- Developing countries -- 20; Electronic books. -- 2